DESAIN DAN UJI COBA E-MODUL KIMIA BERBASIS GUIDED DISCOVERY LEARNING PADA MATERI STRUKTUR ATOM - Refina Salsabila; Ardiansyah Ardiansyah; Yuni Fatisa; Ira Mahartika (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2025)
This research was instigated with Guided Discovery Learning based e-module learning medium that was not yet available to assist teachers in explaining learning material.  This research aimed at producing a learning medium, finding out validity and practicality levels of Guided Discovery Learning based chemistry e-module developed on Atomic Structure lesson.  It was Research and Development (R&D) with Design & Development (DDR) model.  The subjects of this research were 10 the eleventh-grade students of class 1 at Senior High School of Muhammadiyah 1 Pekanbaru, 2 Chemistry subject teachers, a media expert lecturer, and a material expert lecturer.  Questionnaire and interview were the techniques of collecting data.  The research findings showed Guided Discovery Learning based e-module on Atomic Structure lesson that the validity percentages obtained from media and material experts respectively were 87.5% and 98.5% with very valid criteria.  The percentage of teacher practicality test was 82.5% with very practical criteria, and the result of student response test was 82.7% with very good criteria